2020
DOI: 10.3390/biom10040613
|View full text |Cite
|
Sign up to set email alerts
|

3D Cell Culture-Based Global miRNA Expression Analysis Reveals miR-142-5p as a Theranostic Biomarker of Rectal Cancer Following Neoadjuvant Long-Course Treatment

Abstract: Altered expression of miRNAs in tumor tissue encourages the translation of this specific molecular pattern into clinical practice. However, the establishment of a selective biomarker signature for many tumor types remains an inextricable challenge. For this purpose, a preclinical experimental design, which could maintain a fast and sensitive discovery of potential biomarkers, is in demand. The present study suggests that the approach of 3D cell cultures as a preclinical cancer model that is characterized to mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…For example, using 3D culture model with decellularized ECM scaffolds (dECM) allowed to identify fulllength Collagen VI as a driver of breast cancer cell invasion in obesity and metastasis (89). In colorectal cancer, the patterns of expression of miRNA dependent on 3D microenvironment have been characterized, and one of them (miR-142-5p) was identified as a theranostic biomarker (90). As applied to clinical scenarios, the 3D cell culture models incorporating TME are referred to as a "patient's avatar" (91) and "patient-on-a-chip" (92) models, and can allow to identify biomarkers of individual response to the therapy.…”
Section: D Cell Culture Models Incorporating Tme As a Testing Systemmentioning
confidence: 99%
“…For example, using 3D culture model with decellularized ECM scaffolds (dECM) allowed to identify fulllength Collagen VI as a driver of breast cancer cell invasion in obesity and metastasis (89). In colorectal cancer, the patterns of expression of miRNA dependent on 3D microenvironment have been characterized, and one of them (miR-142-5p) was identified as a theranostic biomarker (90). As applied to clinical scenarios, the 3D cell culture models incorporating TME are referred to as a "patient's avatar" (91) and "patient-on-a-chip" (92) models, and can allow to identify biomarkers of individual response to the therapy.…”
Section: D Cell Culture Models Incorporating Tme As a Testing Systemmentioning
confidence: 99%
“…ROC curve analysis showed that miR-21 and miR-328 could provide valuable information for individualizing treatment in rectal cancer patients ( Campayo et al, 2018 ). 3D cell culture-based global miRNA expression analysis revealed increased levels of miR-142-5p in rectal tumor tissue samples after neoadjuvant long course treatment, which may be a theranostic biomarker of rectal cancer ( Kunigenas et al, 2020 ). Low plasma level of exosomal miR-486-5p was associated with organ-invasive primary tumor, which attributed to adverse prognosis of rectal cancer ( Bjornetro et al, 2019 ).…”
Section: Resultsmentioning
confidence: 99%
“…Our results also simultaneously exemplify the possibility of performing CRISPR-Cas9 screens in an in vitro model such as 3D cell culture. In particular, we demonstrated that the sensitivity of 3D cells to radiation is no different from that of 2D cells, despite their growth in matrigel and special culture media [ 17 , 33 , 34 ]. As a result, we irradiated cells with two distinct growth patterns using a standard radiographic screening approach.…”
Section: Discussionmentioning
confidence: 99%